D-Mannose Suppresses γδ T Cells and Alleviates Murine Psoriasis - Li, Mingyang; Cheng, Haiyan; Tian, Dan; Yang, Lu; Du, Xiaonan; Pan, Yuhualei; Zhang, Dong; Mei, Xueling (Frontiers in Immunology, 2022)
Psoriasis is a chronic skin disorder associated with multiple sequelae, such as psoriatic arthritis and cardiovascular diseases. Increasing evidence has shown that γδ T cells, as sources of IL-17A, play critical roles in psoriatic inflammations. However, there still lack effective ways to manipulate these pathogenic γδ T cells, which are less well studied than αβ T cells. The present study aims to characterize the phenotype of γδ T cells and evaluate the impact of D-mannose (a C-2 epimer of glucose) on γδ T cell-mediated psoriasis. We found that skin-draining LN γδ T cells underwent robust proliferation and acquired an IL-17-producing phenotype during psoriasis. The transcriptomic profiles of these psoriatic γδ T cells had elevated glycolytic signatures. Importantly, D-mannose treatment suppressed the γδ T cell reaction and successfully alleviated the local and systematic inflammation induced by imiquimod. The decreased AKT/mTOR/HIF-1α signaling and glycolytic ability may contribute to the suppression of γδ T cells achieved by D-mannose. Our study increased understanding of γδ T cells in psoriasis and promoted D-mannose utilization as a potential clinical application for autoimmune diseases driven by γδ T cells.